Surface complexation modelling of chromium(III) ion exchange by a strong cation exchange resin - Kocaoba, Sevgi; Cetin, Gulten; Akcin, Goksel (TAYLOR & FRANCIS LTD, 2022)
In the present study, the removal of chromium(III) from tannery wastewaters by means of ion exchange was investigated to develop a possible recovery. Experimental investigations were carried out using a strongly acidic cation exchange resin, Amberlite 200. The first part of experiments comprised the measurement of the equilibrium of exchange of Cr(III) for H+. For this purpose different amounts of resins were contacted with a fixed volume of chromium-bearing solution. For evaluation of equilibrium parameters, the surface complexation theory was applied. In the second part, chromium(III) species elimination was studied in column experiments with repeated exhaustion and regeneration series. As a result, it was obtained successful results for removal and recovery of chromium with strong cation exchange resin, Amberlite 200.
Keywords: Chromium; tannery; ion exchange; column and batch experiments; surface complexation theory; WASTE-WATER; HEAVY-METALS; AQUEOUS-SOLUTIONS; HEXAVALENT CHROMIUM; REMOVAL; ADSORPTION; ACID; RECOVERY; PERFORMANCE; EQUILIBRIA; Chemistry; Environmental Sciences & Ecology